Second-round effects after oil-price shocks: evidence for the euro area and Germany - Enders, Almira; Enders, Zeno (Economics letters, 2017)
We investigate second-round effects caused by oil-price shocks, calculating wage responses net of those movements that are induced through CPI changes. Results show no strong evidence for second-round effects in the euro area, and even less so in Germany.